The City Electric : Infrastructure and Ingenuity in Postsocialist Tanzania. - Degani, Michael. (Duke University Press, 2022)
Michael Degani explores how electricity and its piracy in Dar es Salaam, Tanzania, has become a key site for urban Tanzanians to enact, experience, and debate their social contract with the state.